Evolution of Islamic discourse in Turkey - Bozdémir, Michel (Balcanica Posnaniensia. Acta et studia, 2010)
The evolution of Islamic discourse in Turkey reflects the complex interaction between religion, politics, and modernization throughout the twentieth and early twenty-first centuries. The study examines how Islamic expression has transformed from its Ottoman origins through the secular Republican era to the contemporary democratic context. The main objective is to trace the ideological and linguistic shifts within Turkish Islam as it re-enters the political sphere, highlighting the strategies used to adapt religious rhetoric to democratic frameworks. The research relies on qualitative historical and sociolinguistic analysis of political speeches, official policies, and social practices from the late Ottoman Empire to the period following the rise of the Justice and Development Party (AKP) in 2002. Through comparative examination of key stages – the Ottoman, Republican, and democratic – the study identifies the ways Islamic discourse evolved from anti-Western resistance to a more nuanced, politically integrated narrative. The findings reveal that Islamic rhetoric has progressively moved from open confrontation toward strategic moderation. During the secular Republican period (1922–1950), religious discourse was suppressed and privatized, while democracy after 1950 enabled its gradual return to public life. The later emergence of political Islam under leaders such as Necmettin Erbakan introduced a new vocabulary blending nationalism and religion. In the twenty-first century, Islamic discourse has adopted democratic and human rights terminology, reflecting both adaptation to global norms and continuity of religious identity. Ultimately, the study concludes that the Turkish case illustrates a unique synthesis of Islam and democracy, where political pragmatism and rhetorical flexibility have allowed Islamic movements to sustain influence within a formally secular framework.